2013
DOI: 10.1002/pssa.201329308
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-temperature treatment on the hydrogen distribution in silicon oxynitride/silicon nitride stacks for crystalline silicon surface passivation

Abstract: This work investigates a double layer stack system that can be used for surface passivation of crystalline silicon. The stack consists of amorphous silicon-rich silicon oxynitride and amorphous silicon nitride on top. Both layers are fabricated by means of plasma-enhanced chemical vapour deposition. We investigate the stack in terms of changes in the hydrogen content and distribution within the different stack layers due to a high temperature treatment. For that purpose the stack is studied by Fourier-transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Subsequent studies have explored this dielectric system in more detail. Laades et al and Shwab et al corroborated previous findings on the thermal stability of SiON films, and additionally showed that H passivation played a key role in the passivation properties upon high‐temperature firing. Zhou et al systematically studied the plasma deposition parameters, while Brinkmann et al investigated the films’ electrical, optical and structural properties.…”
Section: Materials and Methods For Silicon Surface Passivationsupporting
confidence: 74%
“…Subsequent studies have explored this dielectric system in more detail. Laades et al and Shwab et al corroborated previous findings on the thermal stability of SiON films, and additionally showed that H passivation played a key role in the passivation properties upon high‐temperature firing. Zhou et al systematically studied the plasma deposition parameters, while Brinkmann et al investigated the films’ electrical, optical and structural properties.…”
Section: Materials and Methods For Silicon Surface Passivationsupporting
confidence: 74%
“…To confirm the presence of hydrogen, we performed 15 N nuclear reaction analysis ( 15 N-NRA) on our films. [31,32] In short, the sample is bombarded with 15 N ions (E > 6.385…”
Section: Resultsmentioning
confidence: 99%
“…Both precursor types are made from p-type Cz-Si and all passivation stacks are deposited using Plasma Enhanced Chemical Vapor Deposition (PECVD). The first stack is relying on the chemical passivation with a total thickness of d ≈ 160 nm consisting of a hydrogenated siliconoxynitride (SiON) stack (d ≈ 75 nm) capped with SiN X (d ≈ 85 nm) [8]. The second stack relying on the electrical field effect passivation with a total thickness of d ≈ 150 nm is consisting of an AlO X stack (d < 20 nm) and SiN X capping (d ≈ 130 nm) [9].…”
Section: Methodsmentioning
confidence: 99%